2018
DOI: 10.1016/j.fct.2018.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of genotoxic and carcinogenic alkenylbenzenes in Indonesian jamu and evaluation of consumer risks

Abstract: The consumer risks of jamu, Indonesian traditional herbal medicines, was assessed focussing on the presence of alkenylbenzene containing botanical ingredients. Twenty-three out of 25 samples contained alkenylbenzenes at levels ranging from 3.8 to 440 μg/kg, with methyleugenol being the most frequently encountered alkenylbenzene. The estimated daily intake (EDI) resulting from jamu consumption was estimated to amount to 0.2-171 μg/kg bw/day for individual alkenylbenzenes, to 0.9-203 μg/kg bw/day when adding up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…The study found that in a nationally representative child sample in Indonesia in 2014–15 that the past month prevalence of traditional or herbal medicines use was 6.2%, the past month use of traditional health practitioners was 3.4%, and the past 4-weeks prevalence of the use of traditional medicines and/or traditional practitioners was 8.8%. These general child population prevalences of traditional or herbal and/or complementary medicine use seem higher than found in Italy (2.4% in the past 3 years)16 and USA (0.5% in the past 7 days),13 but similar to Germany (5.8% in the past 7 days),6 and Taiwan (4.7% in the past month) 17. The purpose of consulting the traditional practitioner was mainly massage (86.8%) and treatment for illness (14.8%) in this study.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The study found that in a nationally representative child sample in Indonesia in 2014–15 that the past month prevalence of traditional or herbal medicines use was 6.2%, the past month use of traditional health practitioners was 3.4%, and the past 4-weeks prevalence of the use of traditional medicines and/or traditional practitioners was 8.8%. These general child population prevalences of traditional or herbal and/or complementary medicine use seem higher than found in Italy (2.4% in the past 3 years)16 and USA (0.5% in the past 7 days),13 but similar to Germany (5.8% in the past 7 days),6 and Taiwan (4.7% in the past month) 17. The purpose of consulting the traditional practitioner was mainly massage (86.8%) and treatment for illness (14.8%) in this study.…”
Section: Discussionmentioning
confidence: 56%
“…Parents or guardians should be given health education about herbal medicines and they should also inform health practitioners about the use of herbal medicines of their children in order to prevent negative drug interactions 8. In addition, the producers of herbal medicinal preparations should follow government regulations in producing safe herbal medicines 13,14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite centuries-old culinary and traditional ethnomedicinal usage, development of KGR based functional food could not be possible. The reports on safety and risk assessment of K. galanga preparations is scarce except presence of some harmful alkenylbenzenes in “Jamu” preparations [17,18]. The efficacy with defined mode of action is still a major concern.…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxic and carcinogenic compounds naturally occurring in botanical preparations may include especially alkenylbenzenes (ABs), pyrrolizidine alkaloids (PAs), and aristolochic acids (AAs) (van Den Berg et al 2011). Our previous risk assessment studies on jamu and herbal products from Indonesia reported the presence of these type of constituents at levels that pose a concern for human health at the proposed levels of daily use of jamu products when considering life-long use, indicating a priority for risk management action of the corresponding herbal products (Suparmi et al 2018(Suparmi et al , 2019(Suparmi et al , 2020.…”
Section: Introductionmentioning
confidence: 99%